1976
DOI: 10.1001/archpedi.1976.02120060027006
|View full text |Cite
|
Sign up to set email alerts
|

Children With Superior Intelligence at 7 Years of Age

Abstract: Perinatal and medical information, growth, and the social background of 258 children who, in a prospective study, had superior intelligence at 7 years of age were reviewed. The subjects were divided into three categories on the basis of the results of psychological evaluation at age 7. Comparisons were made between those with superior (intelligence quotient greater than or equal to 120), average (IQ between 80 and 119), and low intelligence (IQ less than or equal to 79). A favorable parental social and educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…[1][2][3][4] Similar associations have been found in adults. 5,6 Maximal brain volume is usually achieved between the ages of 5 and 10 years, 7 but rates of brain growth are highest in the last part of gestation and the first 1 year of life.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…[1][2][3][4] Similar associations have been found in adults. 5,6 Maximal brain volume is usually achieved between the ages of 5 and 10 years, 7 but rates of brain growth are highest in the last part of gestation and the first 1 year of life.…”
mentioning
confidence: 59%
“…Our findings, derived by distinguishing the effects of brain growth during different periods of development, suggest that these associations between head circumference and intelligence in later childhood owe more to the influence of brain growth during infancy than they do to growth after infancy; the findings fit with observations in a cohort of 2023 children that those with IQ scores in the superior range (scores of Ն120) at the age of 7 years had larger head circumferences at 1 year of age than did children whose IQ scores were average (scores of 80 -119). 2 In a recent study, higher IQ scores at the age of 9 years were associated with increased head growth both in the first 9 months of life and between 9 months and 9 years of age, regardless of head size at the start of these periods, but detailed information on growth after 9 months of age was not available. 1 Results from some small studies of very low birth weight infants have indicated that the critical period for catch-up brain growth, in terms of later intelligence, may be confined to the first 1 year of life.…”
Section: Discussionmentioning
confidence: 97%
“…Normal variation in head circumference seems to be associated with cognitive and behavioral development 8-10 . Larger head circumference in infancy is associated with higher IQ scores in childhood 10-12 . The underlying mechanisms however, are poorly understood.…”
Section: Main Textmentioning
confidence: 98%
“…Other research has reported that lower IQ is correlated with smaller head circumference [30-32]. In order to examine this relation, we entered head circumference into our final regression models with the composite score and the area scores as our outcome variables (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…The larger the brain, the higher the test scores [32, 42-44]. Two additional studies have shown that the brain volume achieved by age 1 predicts intelligence in later childhood [31, 45]. Shaw et al [38] demonstrated that the thickness of the cerebral cortex is correlated with intelligence.…”
Section: Discussionmentioning
confidence: 99%